The end of loneliness eaudiobook A novel. - Wells, Benedict (Penguin Audio, 2019)
From internationally bestselling author Benedict Wells, a sweeping novel of love and loss, and of the lives we never get to live “[D]azzling storytelling... The End of Loneliness is both affecting and accomplished — and eternal.” — John Irving "An exquisitely wrought and utterly absorbing meditation upon life, loss and love." — Ian McEwan Jules Moreau’s childhood is shattered after the sudden death of his parents. Enrolled in boarding school where he and his siblings, Marty and Liz, are forced to live apart, the once vivacious and fearless Jules retreats inward, preferring to live within his memories – until he meets Alva, a kindred soul caught in her own grief. Fifteen years pass and the siblings remain strangers to one another, bound by tragedy and struggling to recover the family they once were. Jules, still adrift, is anchored only by his desires to be a writer and to reunite with Alva, who turned her back on their friendship on the precipice of it becoming more. But, just as it seems they can make amends for time wasted, invisible forces – whether fate or chance – intervene.             A kaleidoscopic family saga told through the fractured lives of the three Moreau siblings, alongside a faltering, recovering love story, The End of Loneliness is a stunning meditation on the power of our memories, of what can be lost and what can never be let go. With inimitable compassion and luminous, affecting prose, Benedict Wells contends with what it means to find a way through life, while never giving up hope you will find someone to go with you.